Antecedents of employee engagement – case study of a mid-sized international bank in Malaysia - Khor, Ying Ying (2020)
Employee engagement is widely linked to improved organizational performance. However, maintaining an engaged, committed and productive workforce remains a complex challenge for leaders and managers. Many are unsure what affect employee engagement. They are ill-informed to formulate an effective solution due to their limited knowledge of the subject. This study will examine the antecedents of employee engagement, i.e. leadership, career and job, training and development, and compensation on employee engagement. It also examines the moderating role of gender, age and tenure in these relationships. The research is based on a case study of a multi-national bank in Malaysia, BANKCO. Quantitative survey data was collected from 91 employees in BANKCO. This is supplemented by 14 qualitative interviews carried-out to investigate the leadership style of the Chief Executive Officer (CEO). The study uses both the descriptive and inferential analyses to test the research hypotheses. Results showed that all 4 factors – leadership, career and job, training and development and compensation significantly influence employee engagement. Career and job have the strongest correlation, followed by training and development, and leadership. Compensation has the weakest correlation among all 4 factors. Collectively, these factors explain 74.2% of the variance in employee engagement in BANKCO. The study also found that gender, age and tenure do not moderate the relationship of the antecedents and employee engagement. These findings contribute to existing theoretical and empirical studies on employee engagement and provide important input to managers to help formulate their organization strategies. It will also help other researchers to extend prior studies on employee engagement by exploring different dimensions in variables, scope and time frame. The study will also discuss the limitations and propose several suggestions for future studies.